Dimensions to measure service quality in private higher education institutions. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2011)
Service quality has become an important component of businesses in the service industries across the world. The educational services sector has gone through drastic changes over the decades in realising the vision and mission towards achieving the highest service quality standards to meet its growing customer needs. The modern education has to look to its future survival, beyond its current disciplinary organisation and quality of standards. This involves identifying new modes of providing service quality to enhance the institutions’ competitive advantage and performance.